The Role of Air Pollution in Shaping Urban Cultural Consumption: An Empirical Investigation of PM10 and Movie Consumption in Chinese Cities - Wei Ma; Zhaolei Liu; Yuning Gao (Economies)
This study investigates the nonlinear effects of air pollution on urban entertainment consumption by analyzing daily PM10 levels and movie box office data across 334 Chinese cities from 2012 to 2022, resulting in a total of 1,250,339 observations. Utilizing a two-way fixed effects model and threshold regression framework, we identify three key findings: (1) elevated PM10 concentrations significantly reduce movie attendance, with a 1-unit increase decreasing consumption by 0.0797 units; (2) the inhibitory effect intensifies during weekends and holidays, reflecting heightened sensitivity to pollution during leisure periods; (3) threshold effects emerge, where PM10 exceeding 0.0229 μg/m3 triggers a sharp decline in attendance, while temperature moderates this relationship, amplifying pollution’s negative impact. By integrating meteorological, environmental, and socioeconomic datasets, this research reveals substitution patterns between digital and offline entertainment under pollution stress. The results underscore the necessity for region-specific pollution mitigation strategies, cinema infrastructure upgrades, and dynamic pricing policies to counteract environmental disruptions. These insights advance the interdisciplinary nexus of environmental economics and cultural consumption, offering actionable pathways for sustainable urban development.